2005
DOI: 10.1007/s00421-005-0116-2
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in the responses to endurance and resistance training

Abstract: Large individual differences in the responsiveness of cardiorespiratory fitness (VO2peak) to endurance training have been observed in healthy subjects. We tested the hypothesis that subjects with a poor responsiveness to endurance training might benefit from resistance training in terms of aerobic fitness. The study population consisted of sedentary healthy male and female subjects (n=91, 42+/-5 year) assigned to either a training (n=73) or a control group (n=18). The randomized cross-over study design include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
110
2
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(136 citation statements)
references
References 34 publications
17
110
2
6
Order By: Relevance
“…Partial or overcompensation for ExEE will influence the weight loss associated with an energy deficit. Although various studies have demonstrated individual variability in response to exercise and dietary interventions, [19][20][21][28][29][30][31][32] this is the first study to attempt to characterize the causes of variability. Speculations about potential compensatory responses have been proposed and discussed previously; 22,33 however, these data actually demonstrate the effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partial or overcompensation for ExEE will influence the weight loss associated with an energy deficit. Although various studies have demonstrated individual variability in response to exercise and dietary interventions, [19][20][21][28][29][30][31][32] this is the first study to attempt to characterize the causes of variability. Speculations about potential compensatory responses have been proposed and discussed previously; 22,33 however, these data actually demonstrate the effect.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that there is a large inter-individual variability in improvements in maximal aerobic capacity (VO 2max ) in responses to exercise interventions. 20,21 Therefore, the phenomenon of variability in the VO 2max response to exercise interventions and variability in body weight to dietary interventions has been documented before. However, the phenomenon of variability in the changes in exercise-induced body weight has not been exposed fully.…”
Section: Introductionmentioning
confidence: 99%
“…Hautala et al [9] observed that a strength training program based on the recommendations of the American College of Sports Medicine enhanced the O 2 max in healthy subjects ( O 2 max ~34 ml·kg -1 ·min -1 ). Thus, it appears that changes in these physiological variables are dependent on initial aerobic fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, no hay estudios que comparen los efectos del entrenamiento de fuerza en estos dos tipos de condiciones en variables cardiorrespiratorias: consumo de oxígeno máximo (VO 2máx ), umbral anaeróbico, frecuencia cardíaca (FC), ventilación (VE), etc., teniendo en cuenta que algunos estudios demuestran que programas de fuerza tradicionales en personas sedentarias tienen efectos cardiovasculares similares a actividades de resistencia como andar, correr o trotar (Kaikkonen, Yrjämä, Siljander, Byman, & Laukkanen, 2000;Hautala et al, 2006). Otros trabajos documentan que el entrenamiento de fuerza no es estímulo eficaz para la mejora del consumo máximo de oxígeno (VO 2max ) (Hurley et al, 1984;Dudley, 1988), a no ser que sean personas sedentarias o de baja capacidad funcional.…”
Section: Introductionunclassified